2020
DOI: 10.1177/0974686220966813
|View full text |Cite
|
Sign up to set email alerts
|

Do Women Directors Impact Financial Outcomes? The Indian Evidence

Abstract: This article investigates the impact of women directors on financial outcomes—return and risk of Indian companies. It applies fixed and random effects Tobit regressions to examine the effect of female directors on financial outcomes (returns and risk) of the firm, controlling promoters’ shareholding, leverage, firm growth and age, board size and board meetings. The study does not find any support to agency and resource dependence theories because the proportion of women directors in most Indian boards is too s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 54 publications
0
10
1
1
Order By: Relevance
“…Ahora bien, observando el enfoque modelo GMM, el porcentaje de mujeres en los consejos puede tener efectos negativos sobre el desempeño de la empresa. Estos resultados son similares a Unite et al (2019) y Kumar et al (2020) donde encuentran un efecto negativo, o en algunos casos, no significativo de la diversidad del comité sobre el desempeño de la empresa. Al respecto y en línea con Kumar et al (2020) en este documento se considera que el poco impacto se debe a la escasa existencia de consejeras directoras.…”
Section: Conclusiones Y Discusiónunclassified
“…Ahora bien, observando el enfoque modelo GMM, el porcentaje de mujeres en los consejos puede tener efectos negativos sobre el desempeño de la empresa. Estos resultados son similares a Unite et al (2019) y Kumar et al (2020) donde encuentran un efecto negativo, o en algunos casos, no significativo de la diversidad del comité sobre el desempeño de la empresa. Al respecto y en línea con Kumar et al (2020) en este documento se considera que el poco impacto se debe a la escasa existencia de consejeras directoras.…”
Section: Conclusiones Y Discusiónunclassified
“…Jyothi and Mangalgiri ( 2019 ) examined this linkage for Indian firms during 2005 to 2015 using panel regression model, and find that percentage of women has a significant and positive impact on firm performance. Kumar et al ( 2020 ) investigate the effect of female directors on financial outcomes of Indian firms using fixed and random effect Tobit regression. They find that the women directors do not make much impact in most Indian boards due to their small presence on companies’ boards.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The presence of women directors as a significant portion of the board and their active role in the functioning and governance of companies makes the difference. However, most Indian companies have not gone beyond the minimum requirement of one WD on their boards and therefore, it is more of a tokenism rather than nurturing the culture of gender diverse boards (Kumar et al 2020 ; The Economic Times , Feb 19, 2018). While prescribing governance policies, the policymakers should take note of the fact that women with adequate relevant experience and relevant background should be appointed on boards, and not just the minimum required numbers (Joecks et al 2013 ).…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…While empirical research on the influence of WBoC on FP has shown inconclusive results, many studies have shown that the presence of WBoC either has a lower impact on FP (Adams & Ferreira, 2009;Akpan & Amran, 2014;Darmadi, 2013;Fauzi & Locke, 2012;Ghafoor, Duffour, Khan & Khan, 2022;Mubarka & Kammerlander, 2022;Roudaki, 2018) or a positive impact on FP (Dissanayake, Jeyaraj & Nerur, 2021;Mubarka & Kammerlander, 2022;Ramadan & Hassan, 2022;Tran, Nguyen& Wang, 2022). Meanwhile, other studies (Hatane, Winoto, Tarigan & Jie, 2022;Kumar, Nigam & Singh, 2020;Shukeri, Shin & Shaari, 2012;Wang, Abbasi, Babajide & Yekini, 2019) have also shown that the presence of WBoC has no impact on FP.…”
Section: Introductionmentioning
confidence: 99%